Dental anxiety in adult patients treated by dental students: A systematic review. Issue 7 (13th May 2020) - Goh, Elizabeth Z.; Beech, Nicholas; Johnson, Nigel R.
Abstract: Purpose/objectives: Dental anxiety is common and can propagate a vicious cycle of dental neglect and anxiety‐provoking treatment. Patient, procedural, and operator factors are important contributions. This review aims to explore risk factors for dental anxiety in adult patients treated by dental students, in order to improve awareness of relevant factors and aid patient management. Methods: Systematic searching of PubMed and Scopus databases was performed. Inclusion criteria were: studies assessing at least 1 risk factor for dental anxiety in patients aged 18 years and above treated by dental students, with use of a specific measurement scale for dental anxiety. Exclusion criteria were: duplicates, non‐English publications, non‐full‐text publications, studies with a pediatric sample. Results: Nine hundred thirty‐one articles were identified. Eight eligible articles representing 1702 patients were included. Seven studies had a cross‐sectional design and 1 study had a pretreatment/posttreatment design. Sixteen factors for dental anxiety were assessed. A significant correlation ( P < 0.05) was found for: age (younger), gender (female), general/waiting room anxiety, irregular dental attendance, invasive treatment, poor emotional well‐being, postponement of dental visit due to anxiety, previous negative dental experience and village residence. No significant correlation was found for: education, employment, income, perceived oral health, presence of a previous dental visit, symptom duration and time since last dental visit. Conclusions: These findings provide a good foundation for future research, but clinical generalization is limited by the heterogeneity among included studies. A well‐structured comparison of risk factors for dental anxiety between patients treated by dental students and dentists is required.